The international leader and his moral code according to the theory of realism - Monika M. Brzezińska (Chrześcijaństwo-Świat-Polityka)
As analysis shows, every international leader (whether a Hegemon, Stabilizer or other) has his own moral code. They differ from each other, which generates conflicts and does not foster cooperation. The more versatile the values, the greater the chance of peace, but because a realistic leader is characterized by untenable and selfish morality, which is neither lasting nor certain.